2020
DOI: 10.1177/0018726720938118
|View full text |Cite
|
Sign up to set email alerts
|

Leader and organizational identification and organizational citizenship behaviors: Examining cross-lagged relationships and the moderating role of collective identity orientation

Abstract: People may identify with multiple entities at work, but how are different foci of identification related and how do they influence extra-role work behaviors? Drawing from social identity theory, our article examines: (a) the potential bidirectional relationship between leader and organizational identification; (b) the mediating role of organizational identification on the relationship between leader identification and organizational citizenship behavior (organization-targeted, OCBO); and (c) the moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 66 publications
2
26
0
Order By: Relevance
“…Furthermore, inclusive leaders encourage employees to express opinions. When the mission of an organization is aligned with the will of individuals, career integration is enhanced (Marstand et al, 2020 ). Finally, inclusive leaders emphasize creating a fair organizational atmosphere and do not casually blame employees for their mistakes.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, inclusive leaders encourage employees to express opinions. When the mission of an organization is aligned with the will of individuals, career integration is enhanced (Marstand et al, 2020 ). Finally, inclusive leaders emphasize creating a fair organizational atmosphere and do not casually blame employees for their mistakes.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…To benefit from sustainability, enterprises have begun to emphasize collaboration between organizations and individuals. In particular, leadership, an organizational factor, has crucial influence on career sustainability and has been widely discussed in the context of stimulating work passion (Ho and Astakhova, 2020 ), reducing burnout (Prastio et al, 2020 ), clearing identity orientation (Marstand et al, 2020 ), and increasing career satisfaction (Chang et al, 2020 ). All such factors are closely related to career sustainability, but few studies have identified a direct link between leadership and career sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, organizational identification can stimulate the motivation of employees to meet organizational needs and prompt employees to regard themselves and the organization as a community of interests and pay more attention to the collective interests of the organization ( Buil et al, 2019 ; Wang and Liu, 2020 ). When employees identify with the organization, they will be more committed to working for the interests of the organization, and organizational identification can significantly improve employee performance and organizational citizenship behavior ( Buil et al, 2019 ; Marstand et al, 2020 ). On the other hand, organizational identification can motivate employees to maintain a positive organizational identity ( Shuman et al, 2018 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…According to the normative conflict model, organizational identification is an important motivation for employees to raise dissent, and individuals with high organizational identification will put organizational interests above personal interests ( Packer and Chasteen, 2010 ; Packer and Miners, 2014 ). Literature on organizational identification also shows that organizational identification is often closely related to employees’ proactive behavior ( Marstand et al, 2020 ; Shahjehan et al, 2020 ). As the spokesperson of an organization, ethical leadership’s care and respect for employees can promote employees’ identification with the organization ( Zhu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Simons (2002) had proposed that BI is likely to predict follower prosocial behaviors directly (as explained above) or through its impact on followers' attitudes. Based on Simons' (2002) theory and research on follower identification that has shown that identification with leader and with organization enhance follower OCB (e.g., Marstand et al 2020; Zhang and Chen 2013), we examine leader identification and organizational identification as mediating mechanisms in leader and organizational BI and follower OCBO relationships.…”
Section: Behavioral Integrity and Organizational Citizenship Behaviorsmentioning
confidence: 99%